2018
DOI: 10.1021/acs.jafc.8b00829
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic Mannan-Oligosaccharides Augment the Hypoglycemic Effects of Metformin in Correlation with Modulating Gut Microbiota

Abstract: Type 2 diabetes (T2D) induced by obesity and high-fat diet is significantly associated with gut microbiota dysbacteriosis. Because the first line clinical medicine of metformin has several intestinal drawbacks, combination usage of metformin with a prebiotic of konjac mannan-oligosaccharides (MOS) was conceived and implemented aiming to investigate whether there were some intestinal synergetic effects and how MOS would function. Composite treatment of metformin and MOS demonstrated synergistic effects on ameli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 50 publications
6
78
0
3
Order By: Relevance
“…Additionally, in male mice, DHA selectively increased butyrate‐producing Coprococcus [ 47 ] while suppressed pro‐inflammatory species Streptococcus [ 48 ] and p‐75‐a5 which were strongly correlated with HOMA‐IR and LPS production in our study. EPA selectively enriched the abundances of Mucispirillum schaedleri [ 49 ] and Barnesiella [ 50 ] which have been suggested to counteract colitis in mice and elevated S24‐7 [ 51 ] and Barnesiella [ 52 ] linked with ameliorated glucose metabolism, whereas substantially abolished SCFA‐producing Clostridium XlVa [ 53 ] which might explain the unchanged levels of propionate and butyrate in male mice. In female mice, DHA specifically decreased the abundance of pro‐inflammatory Enterorhabdus [ 54 ] and promoted the growth of butyrate‐producing Intestinimonas [ 55 ] and Bacteroides acidifaciens [ 56 ] which were shown to prevent obesity and improve insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in male mice, DHA selectively increased butyrate‐producing Coprococcus [ 47 ] while suppressed pro‐inflammatory species Streptococcus [ 48 ] and p‐75‐a5 which were strongly correlated with HOMA‐IR and LPS production in our study. EPA selectively enriched the abundances of Mucispirillum schaedleri [ 49 ] and Barnesiella [ 50 ] which have been suggested to counteract colitis in mice and elevated S24‐7 [ 51 ] and Barnesiella [ 52 ] linked with ameliorated glucose metabolism, whereas substantially abolished SCFA‐producing Clostridium XlVa [ 53 ] which might explain the unchanged levels of propionate and butyrate in male mice. In female mice, DHA specifically decreased the abundance of pro‐inflammatory Enterorhabdus [ 54 ] and promoted the growth of butyrate‐producing Intestinimonas [ 55 ] and Bacteroides acidifaciens [ 56 ] which were shown to prevent obesity and improve insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…MOS, one of the potent prebiotics, has been widely reported to possess antioxidant, anti‐inflammatory, anti‐atherosclerosis, and anti‐virus bioactivities and to improve STZ‐induced diabetes . Importantly, MOS supplementation could improve the gut microbiota balance and mediate the microbial synthesis of metabolites . A recent report indicated that Konjaku flour attenuated HFD‐induced obesity and gut microbiota imbalance in 3 week weaning mice .…”
Section: Discussionmentioning
confidence: 99%
“…[20] Importantly, MOS supplementation could improve the gut microbiota balance and mediate the microbial synthesis of metabolites. [26,37,48] A recent report indicated that Konjaku flour attenuated HFD-induced obesity and gut microbiota imbalance in 3 week weaning mice. [26] MOS is one of the major components of Konjaku flour, and its polymerization degree is 2−10.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations